The Role of Information and Communication Technologies in Africa’s Digital Transformation - Khanova Olena V.; Shynkarenko Oleksii S. (Problemi Ekonomiki)
The article is aimed at studying the state of the Internet in African countries, analyzing the experience of its use depending on the level of development of countries, as well as forming prospects for the growth of the introduction of information and communication technologies (ICT) in the context of significant infrastructure challenges, in particular access to electricity. The state of electricity supply in urban and rural areas of African countries, which is a basic condition for the introduction of modern ICT and digital transformation, has been analyzed. A comparative analysis of structural changes in access to electricity for the period 2017–2023 for 43 countries of the African region was carried out. It is found that most countries demonstrate positive dynamics of access to electricity, but some countries remain significantly backward due to economic instability, conflicts and destruction of infrastructure. A forecasting of the prospects for 3G and 4G network coverage, which are key elements of digital infrastructure, is carried out. It is identified that by 2026 the full coverage of the 3G network in Africa may reach 99.41%, which will create prerequisites for the further introduction of 4G. Next, the gradation of African countries in terms of the level of informatization and digital transformation has been carried out. The group with a high level of informatization includes such countries as South African Republic, Egypt, Morocco, Kenya, Tunisia, Algeria, which demonstrate a high level of access to the Internet and significant structural shifts in the development of ICTs. The countries with an average level of digital integration, such as Nigeria, Senegal, Tanzania, Rwanda, Zambia, need further investments in infrastructure. The least developed countries, which are Chad, Somalia, Burkina Faso, face critical problems of access to electricity and low levels of informatization. A number of scientific and practical recommendations are formulated, which provide for the use of alternative energy sources, attracting international investments, introducing educational programs on digital literacy for young people, creating conditions for the development of local startups in the field of ICT and energy. Particular attention is paid to the role of the African Union in coordinating the efforts of the countries of the region to bridge the digital divide, ensure sustainable development and integrate Africa into the global digital economy.